2021
DOI: 10.25122/jml-2021-0304
|View full text |Cite
|
Sign up to set email alerts
|

Cancer testis antigen XAGE-1 is a promising marker for the diagnosis and treatment of ovarian cancer

Abstract: Cancer testis antigens have been discovered in various cancers, and several studies have suggested that since they exhibit such distinct patterns of expression, these antigens might be attractive targets for cancer detection and immunotherapy. Our work attempted to clarify the function played by cancer-testis antigens in ovarian cancers, notably in the XAGE1 gene. The investigation was conducted on 74 tissue samples from newly diagnosed patients with ovarian cancer. The control group included twenty-eight beni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Subsequently, we found that the expression of OY‐TES‐1 protein in ovarian cancer was 81%, the positive rate of epithelial ovarian cancer was 66.4% (71/107), and the positive rate of nonepithelial ovarian cancer was 14.9% (16/107) 34 . Other studies showed that the expression of XAGE1 (CT12 family) in ovarian cancer was higher than that in benign ovarian tumor (least signifcant difference = 2.319) and was correlated with stage and pathological type 86 . A report showed high frequency of SPAG9 (CT89) mRNA in serous carcinoma (88%), mucinous carcinoma (100%), and transparent carcinoma (100%), respectively.…”
Section: Expression and Clinical Significance Of Cta In Ovarian Cancermentioning
confidence: 97%
See 3 more Smart Citations
“…Subsequently, we found that the expression of OY‐TES‐1 protein in ovarian cancer was 81%, the positive rate of epithelial ovarian cancer was 66.4% (71/107), and the positive rate of nonepithelial ovarian cancer was 14.9% (16/107) 34 . Other studies showed that the expression of XAGE1 (CT12 family) in ovarian cancer was higher than that in benign ovarian tumor (least signifcant difference = 2.319) and was correlated with stage and pathological type 86 . A report showed high frequency of SPAG9 (CT89) mRNA in serous carcinoma (88%), mucinous carcinoma (100%), and transparent carcinoma (100%), respectively.…”
Section: Expression and Clinical Significance Of Cta In Ovarian Cancermentioning
confidence: 97%
“…34 Other studies showed that the expression of XAGE1 (CT12 family) in ovarian cancer was higher than that in benign ovarian tumor (least signifcant difference = 2.319) and was correlated with stage and pathological type. 86 A report showed high frequency of SPAG9 (CT89) mRNA in serous carcinoma (88%), mucinous carcinoma (100%), and transparent carcinoma (100%), respectively. Its protein expression had a high frequency (90%).…”
Section: Expression and Clinical Significance Of Cta In Ovarian Cancermentioning
confidence: 98%
See 2 more Smart Citations